Progress in the study of the effects of selective serotonin reuptake inhibitors (SSRIs) on the reproductive system - Feng, Yu; Qu, Xiaoyan; Hao, Hua (Frontiers in Pharmacology, 2025)
In recent years, the increasing number of infertility cases has led to a greater research focus on the reproductive toxicity of drugs due to the fact that some classes of pharmacotherapeutic agents have been found to exert deleterious effects on the reproductive system. Depressive disorders are a class of common mental illnesses that seriously damage human health. The variety of antidepressant drugs is large and the incidence of adverse effects is high. Selective serotonin reuptake inhibitors (SSRIs), as the first-line drugs for the treatment of depression, have remarkable efficacy, but at the same time there is a widespread abuse of them, which not only creates an unfavorable impact on one’s own reproductive system, but also may cause reproductive damage to other non-target populations through pathways, such as the water column. The review provides an introduction to the reproductive toxicity of SSRIs from the aspects of male and female germ cell genesis, embryonic development, reproductive system maturation, and environmental contamination, and it briefly describes the potential mechanisms underlying SSRI-induced reproductive toxicity.